Reclamation of the Center Point of Indonesia and the Impact of Tourism in Makassar City - Nur, Andi Cudai; Arhas, Sitti Hardiyanti; Aslinda, Andi; Rusdi, Rusdi (Program Pascasarjana Universitas Negeri Makassar, 2024)
A fairly large and controversial reclamation project in Indonesia is the reclamation project at the Center Point of Indonesia (CPI), Makassar. The project aims to expand the city area and create a new business center in Makassar, the largest city in South Sulawesi. CPI reclamation is designed to increase tourist attractions, increase commercial areas, and overcome land limitations in urban areas. This study aims to determine the impact of reclamation in increasing tourism in Makassar. The type of research used in this study is descriptive research that aims to dig deeper into the impact of reclamation in increasing tourism in Makassar. Data collection is carried out by interviews and documentation. Interviews were conducted with 60 CPI visitors, and 60 MSMEs during Car Free Day. The data analysis used is data collection, data condensation, presentation, and conclusion. The results of the study show that CPI reclamation has increased Makassar tourism. This happens because CPI offers interesting places that can be enjoyed by the public.